Integrated Assessment of Climate Change Impacts and Urban Resilience From Climate and Hydrological Hazards to Risk Analysis and Measures - Russo, Beniamino; Martínez-Gomariz, Eduardo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book brings together recent research related to urban resilience, in particular, taking into account climate change impacts and hydrological hazards. Due to the complexity of our cities, which are vulnerable and continuously evolving systems, urban resilience should be considered as a transversal and multi-sectorial issue, affecting different urban services, several hazards, and all the steps of the risk management cycle. Within this context, the different pieces of research that form this book deal with the topics of multi-risk and urban resilience assessment, analysis of cascading effects, and the proposal and prioritization of adaptation measures and strategies to cope with climate-related hazards through multi-criteria analysis.